Practical exploration on the construction of data asset management system - Guohe LI; Zheng FENG; Zhuoyu WANG; Yong SUN; Yang GUO; Qiguo SAN (Dianxin kexue)
With the change of policy environment and the upgrading of information technology,the big data strategy has officially risen to the national strategy.Digital China construction is accelerating in all directions,and data asset management has received unprecedented attention.The construction of data asset management system has become an inevitable choice and inevitable trend for enterprises to cope with the requirements of the era of big data.Data value mining needs to provide protection through data asset management system.Focusing on the problems existing in the big data management and control of State Grid Xinyuan Co.,Ltd.,based on the advanced and mature data asset management knowledge system at home and abroad,combined with the company’s business characteristics and business needs,research on data asset management system was carried out from three aspects:organizational system,management and control system and system platform.The research of data asset management system laid foundation for the construction practice of the later data asset management system,and provided effective data for improving corporate governance capabilities,optimizing core resource allocation,promoting the birth of big data in the pumped storage industry and the sustainable and healthy development of corporate data assets.